Exploring pharmacists' views on the potential use of e-cigarette as a smoking cessation aid - Mohd Nizar, Muhammad Syahmi (2016)
Electronic cigarette or e-cigarette as abbreviated in the society was firstly invented by a pharmacist. The pharmacist's name is Hon Lik and he invented e-cigarette with an intention to help smokers quit tobacco smoking. The main reason was that, unlike tobacco smoking, e-cigarette delivers vapour without tobacco. However, in recent issues, the society started to doubt the purpose of e-cigarette devices. Statistics claims that there was an increase of prevalence among the use of e-cigarette devices among young teenagers who are smokers or non-smokers. However, no study was done in order to justify the claims made and especially to understand the real use of electronic cigarettes. So far little is also known about the perceptions of community pharmacists as a health care provider in this topic. The objective of this study is to explore the view of pharmacists on the use of e-cigarettes. Data were collected through face-to-face interviews, audio recorded, and transcribed verbatim. The sample size was only eight respondents due to limitations that cannot be counter measured. The samples were community pharmacist around Klang Valley area which had been selling nicotine replacement therapy products. The interview had mixed opinion where initially the respondents felt negative towards the idea of electronic cigarettes.